Crystal structure of RPB5, a universal eukaryotic RNA polymerase subunit and transcription factor interaction target - Todone, Flavia (National Academy of Sciences, 2000)
Eukaryotic nuclei contain three different types of RNA polymerases (RNAPs), each consisting of 12–18 different subunits. The evolutionarily highly conserved RNAP subunit RPB5 is shared by all three enzymes and therefore represents a key structural/functional component of all eukaryotic RNAPs. Here we present the crystal structure of the RPB5 subunit from Saccharomyces cerevisiae. The bipartite structure includes a eukaryote-specific N-terminal domain and a C-terminal domain resembling the archaeal RNAP subunit H. RPB5 has been implicated in direct protein-protein contacts with transcription factor IIB, one of the components of the RNAP(II) basal transcriptional machinery, and gene-specific activator proteins, such as the hepatitis B virus transactivator protein X. The experimentally mapped regions of RPB5 involved in these interactions correspond to distinct and surface-exposed α-helical structures.